Model Development Service Jamkesmas Patient in Hospital Dr . M. Djamil Padang for be World's Best in Ministry in Sumatra - -, Nurlina -; Naini, Ineng - (Manajemen dan Kewirausahaan; Vol 6 No 2 (2015): Published in May 2015, 2015)
This study aims to determine the model of patients’ services in the JAMKESMAS participants Hospital dr. M. Djamil Padang, and to find out the Root Cause Analysis of the problem and the way out (possible solution) of the problemin order to make the vision of the hospital fore most hospitals in Sumatra. This research  used a qualitative methods with 90 patients as respondents will be interviewed as well as questioners by the patient or the patient's family. The finding of this researchis found that medical and non-medical personnel are less effective. After docters’diagnoses, they should meet docters’ specialist but they got services from the docters’ residents. They only got services from the docters’ specialist by telephone. It certainly took a long process for resident physicians to perform treatments and got labor’s services because there is only one admin/laboran at the labor. The solutions are: 1) Docters’ specialist should give a high services 2) Docters’ specialist have much time in IGD3) Provided religious learning to the docters’ specialists.(4) There is a punishment to them who don’t obey the rules. 5) To increase the higher services based on social community. 6). To add numbers of admin/ laboran.